UNRAVELLING THE THREADS OF HOSPITAL ACQUIRED INFECTIONS: A COMPREHENSIVE STUDY OF EPIDEMIOLOGY, PREVALANCE AND RISK FACTORS. - Khaja Ashrafuddin1*, Dr. Hemant Kumar Sharma2 (Chelonian Research Foundation, 2022)
Objective: Healthcare-acquired infections (HAIs) are localized or systemic conditions caused by infectious agents or toxins, often appearing over 48 hours after hospitalization, affecting specialized treatment, hemodialysis, chemotherapy, institutionalized individuals, and nosocomial microorganisms. Methods: The study was a prospective observational study conducted at a tertiary care hospital. Data was analyzed using a form which was analyzed further and results are reported. Results: The study involved 97 participants with comorbidities like diabetes, hypertension, and pulmonary disease. Risk factors for developing HAI included central line presence, urinary catheter presence, mechanical ventilation, antimicrobial exposure, and chronic conditions. Commonly acquired HAIs included CLABSI, CAUTI, SSI, and VAP, with 44 subjects with CAUTI, 22 with VAP, 18 with CLABSI, and 12 with SSI. Conclusion: Hospital acquired infections (HAIs) are a global concern due to antibiotic-resistant bacteria, particularly in developing countries. Most hospital-acquired infections (HAIs) are spread through surface contact, catheters, intravenous lines, or surgical incisions. Conventional antibiotics are ineffective, leaving only last-resort antibiotics as treatment options. Healthcare professionals are concerned, prompting governmental, academic, and medical organizations to implement multiple-intervention infection control strategies to reduce mortality, morbidity, and medical costs. Keywords: Hospital acquired infections, HAI, CLABSI, CAUTI, SSI, and VAP.